2013
DOI: 10.1055/s-0032-1328156
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the Proliferation of Human Tumor Cell Lines by Peptidase Inhibitors from Bauhinia Seeds

Abstract: In cancer tumors, growth, invasion, and formation of metastasis at a secondary site play a pivotal role, participating in diverse processes in the development of the pathology, such as degradation of extracellular matrix. Bauhinia seeds contain relatively large quantities of peptidase inhibitors, and two Bauhinia inhibitors were obtained in a recombinant form from the Bauhinia bauhinioides species, B. bauhinoides cruzipain inhibitor, which is a cysteine and serine peptidase inhibitor, and B. bauhinioides kalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…To date, vortioxetine has been the novel antidepressant for treatment of major depressive disorder, although its anti-tumor effects on GC have not yet been fully investigated. The main biological characteristics of a developing tumor malignancy, including GC, are the abnormal proliferation, migration and invasion of cells, [30,31]. The results of the cell function assay demonstrated that vortioxetine inhibited tumor progression of GC by inhibiting cell proliferation, invasion and migration.…”
Section: Discussionmentioning
confidence: 99%
“…To date, vortioxetine has been the novel antidepressant for treatment of major depressive disorder, although its anti-tumor effects on GC have not yet been fully investigated. The main biological characteristics of a developing tumor malignancy, including GC, are the abnormal proliferation, migration and invasion of cells, [30,31]. The results of the cell function assay demonstrated that vortioxetine inhibited tumor progression of GC by inhibiting cell proliferation, invasion and migration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KLK6 has been identified as a marker of poor prognosis in colon and ovarian cancer patients [ 34 , 35 ]. Natural and recombinant kallikrein inhibitors are cytotoxic to a wide range of human cancer cells in vitro [ 44 , 45 ], but no data are available to demonstrate chemopreventive or chemotherapeutic efficacy in vivo . In this regard, protease inhibitors such as Bowman-Birk Inhibitor Complex (BBIC) have been demonstrated to inhibit carcinogenesis in a broad range of experimental models (reviewed in [ 46 ]), including the hamster cheek pouch model of oral neoplasia [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…BbKI is the first plant-derived inhibitor of the primary structure set described that is an inhibitor of tissue kallikrein [ 17 , 18 ]. Indeed, rBbKI was effective in inhibiting the viability of tumor cell lines [ 19 ].…”
Section: Introductionmentioning
confidence: 99%